Adoration Euphoria in K-Pop: Influence Celebrity Worship to Psychological Well-Being in Early Adult Women - Nurhayati, Siti Rohmah; Sary, Puspa (Jurnal Psikologi Teori dan Terapan, 2024)
Abstract Background: One of the reasons someone has psychological well-being the low one is celebrity worship behavior or what is commonly known as celebrity worship. Objective: This study aims to determine the effect of celebrity worship on psychological well-being in early adult women K-pop lovers in Special Region of Yogyakarta. Method: This research uses a quantitative approach. The research sample consisted of 400 participants with the criteria being early adult female K-pop fans aged 18-25 who live in Special Region of Yogyakarta. Data analysis were carried out using multiple regression techniques to determine the existence of an influence of celebrity worship on psychological well-being. Result: Celebrity worship influences psychological well-being. Variablecelebrity worship provides an effective contribution of 4.4% to psychological well-being. Dimensions of borderline-pathological tendency partially influence psychological well-being entertainment-social value and intense personal feelings do not affect psychological well-being. Conclusion: There is only one internal dimension of celebrity worship that influences the psychological well-being of K-pop-loving early adult women in DIY, and that is borderline-pathological tendency.   Abstrak Latar belakang: Salah satu penyebab rendahnya kesejahteraan psikologis seseorang adalah karena perilaku pemujaan selebriti atau yang biasa disebut dengan celebrity worship. Tujuan: Penelitian ini bertujuan untuk untuk mengetahui pengaruh celebrity worship  terhadap psychological well-being pada wanita dewasa awal pecinta K-pop di Daerah Istimewa Yogyakarta. Metode: Penelitian ini menggunakan pendekatan  kuantitatif. Sampel penelitian berjumlah 400 partisipan dengan kriteria wanita dewasa awal penggemar K-pop berusia 18-25 tahun yang tergabung berdomisili di Daerah Istimewa Yogyakarta. Analisis data dilakukan dengan teknik regresi berganda untuk mengetahui adanya pengaruh celebrity worship  terhadap psychological well-being. Hasil: Celebrity worship  berpengaruh terhadap psycological well-being. Variabel celebrity worship  memberikan sumbangan efektif sebanyak 4.4% terhadap psychological well-being. Dimensi borderline-pathological tendency secara parsial berpengaruh terhadap psychological well-being entertainment-social value dan intense-personal feeling tidak berpengaruh terhadap psychological well-being. Kesimpulan: Hanya terdapat satu dimensi dalam celebrity worship berpengaruh terhadap psychological well-being pada wanita dewasa awal pecinta K-pop di Daerah Istimewa Yogyakarta, yaitu borderline-pathological tendency.